Effect of plant growth regulators on growth, physiological behaviour and flower quality of ’Cassini’ tulip(Tulipa gesneriana ) - KHAN, F U; MALIK, F A; KHAN, F A; SIDDIQUE, M A A A (The Indian Journal of Agricultural Sciences, 2011)
Application of gibberellic acid (GA3) as pre-soaking plus foliar spray resulted in improved growth and flowering attributes while as paclobutrzol (PP333) as bulb dip plus foliar spray repress plant growth but improved scape thickness and flower diameter. GA, caused hastening of flowering while PP333 resulted in delayed flowering in tulip. The field life of tulip flower was significantly extended by GA, treatments in comparison to control and bulb dip was found more superior over foliar sprays.